Lingkungan Hidup dalam Perspektif Fikih - M. Th, Asmuni (Unisia, 2010)
The following article tries to explain Islamic law on environmental issues. Islamic Law should accomadate every sphere of human life, including the management of environ ment. In this relation, the position of human as Allah's vicegerence {Khalifah Allah) must responsible for their own deeds on the earth. For that reason, to formulate the contextual Islamic law on environmental problems, there are five principles, the principle of language, the goal of syari'ah. the condidition and the situation of society, the mutual complete, and rational. According to the writer, based on five principles should formulate and apply intellectual exercise of Islam (Ijtihad) to solve and to develop environment fiqh.